2018
DOI: 10.15587/1729-4061.2018.142175
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of capabilities of military groupings (forces) based on the functional group “Engage”

Abstract: Запропоновано пiдхiд щодо оцiнки спроможностей угруповань вiйськ (сил) на основi використання комбiнаторного методу з обмеженою базою аргументiв на прикладi функцiональної групи спроможностей "Застосування". Оцiнка спроможностей угруповання вiйськ (сил) здiйснюється в рамках оборонного планування з метою визначення перспективного складу Збройних Сил України (сил оборони). Сучасний Порядок оцiнки спроможностей угруповання вiйськ (сил) в Збройних Силах України ґрунтується на експертних методах оцiнювання. Недолi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Study [15] concluded that the functional capabilities groups identified in the Catalog could be divided into three classes (technical equipment, training levels, and institutional capabilities). It is also proposed to group functional capability groups into a specific integrated capability using regression analysis methods.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Study [15] concluded that the functional capabilities groups identified in the Catalog could be divided into three classes (technical equipment, training levels, and institutional capabilities). It is also proposed to group functional capability groups into a specific integrated capability using regression analysis methods.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Paper [4] made an attempt to carry out a comprehensive comparative assessment of both the groups of troops and the samples of weapons and military equipment using a capabilities-based defense planning procedure. For this purpose, the authors proposed one of the methods of regression analysis (a combinatorial method with the limited base of arguments).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Analysis of approaches to choosing the rational variant of an armament sample [1][2][3][4][5][6][7][8][9][10][11][12] reveals the lack of a general scientific and methodical apparatus for solving the set problem. Typically, assessing the importance of characteristics for armament and military equipment employs the approaches defined by the specificity of objects that are compared.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Bychenkov at al. proposes implementing a quantitative expert system while breaking capabilities into functional groups [ 40 ]. The study describes the design of an expert system based on a single selected functional group called “engage”.…”
Section: Introductionmentioning
confidence: 99%